Brincar e Contar Histórias com Crianças com Transtorno do Espectro Autista: Mediação do Adulto - Deliberato, Débora [UNESP]; Adurens, Fernanda Delai Lucas [UNESP]; Rocha, Aila Narene Dahwache Criado [UNESP] (Associação Brasileira de Pesquisadores em Educação Especial - ABPEE, 2021)
The aim of this study was to describe the mediation of adults and the communication skills of two children with Autism Spectrum Disorder, in playful situations, through storytelling. The activities were carried out in a Specialized Rehabilitation Center in a city in the hinterlands of the state of São Paulo, Brazil. Two male children aged 2 years and 9 months and 3 years and 3 months old were selected. Data were collected during six months, through weekly activities with families and health professionals, following an intervention program with stories. The activities were filmed and recorded through the field diary. The categories and subcategories were identified after the videos were transcribed and the field diary records were incorporated into a single text organized in time sequence of the activities. The categories and subcategories identified in relation to the objectives of this study were: a) adult mediation: modeling, questioning and intonation of the adult interlocutor’s voice, use of supplementary and alternative communication systems: tangible system, pictographic system and combined mediation; b) skills of expression: verbal and vocal expression, non-verbal and vocal expression, non-verbal and non-vocal expression, combined expressions. The results illustrated the importance of adult mediation in the activity of storytelling as an instrument for accessing language and communicative skills of the children involved during the mediation process.

O objetivo deste estudo foi descrever a mediação do adulto e as habilidades comunicativas de duas crianças com Transtorno do Espectro Autista, em situações lúdicas, por meio da narração de histórias. As atividades foram realizadas em um Centro Especializado em Reabilitação de uma cidade do interior do estado de São Paulo. Foram selecionadas duas crianças do gênero masculino com 2 anos e 9 meses e 3 anos e 3 meses de idade. Os dados foram coletados durante seis meses, por meio de atividades semanais com as famílias e profissionais da saúde, seguindo um programa de intervenção com histórias. As atividades foram filmadas e registradas por meio do diário de campo. As categorias e as subcategorias foram identificadas após a transcrição dos vídeos e incorporação dos registros do diário de campo em um texto único organizado em sequência temporal das atividades. As categorias e as subcategorias identificadas em relação aos objetivos deste estudo foram: a) mediação do adulto: modelação, questionamento e entonação da voz do adulto interlocutor, uso de sistemas suplementares e alternativos de comunicação: sistema tangível, sistema pictográfico e mediação combinada; b) habilidades de expressão: expressão verbal e vocal, expressão não verbal e vocal, expressão não verbal e não vocal, expressões combinadas. Os resultados ilustraram a importância da mediação do adulto na atividade da narração de histórias como um instrumento para o acesso à linguagem e às habilidades comunicativas das crianças envolvidas durante o processo de mediação.
Playing and Telling Stories with Children with Autism Spectrum Disorder: Mediation of Adults
Keywords: Special Education; Language mediation; Storytelling; Early Childhood Education; Alternative Communication; Educação Especial; Mediação da linguagem; Narração de histórias; Educação Infantil; Comunicação Alternativa